2010
DOI: 10.3892/ijo_00000735
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide reductase subunit M1 assessed by quantitative double-fluorescence immunohistochemistry predicts the efficacy of gemcitabine in biliary tract carcinoma

Abstract: Abstract. Gemcitabine is a commonly used chemotherapeutic agent for advanced biliary tract carcinoma (BTC), although its efficacy is insufficient. Therefore, it is essential to establish new diagnostic methods, which can predict responders before the treatment. The aim of this study is to identify the most reliable chemoresistance marker to gemcitabine in BTC among the 4 molecules (hENT1, dCK, RRM1 and RRM2) involved in gemcitabine metabolism. The expression of 4 molecules were investigated in 5 BTC cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
0
1
Order By: Relevance
“…For example, several retrospective studies have evaluated the association between RRM1 expression and survival outcomes in patients with BTC. Although two studies found that low RRM1 expression was significantly associated with prolonged OS [23,24], two other studies found no significant differences between patients with high and low RRM1 expression [15,25]. The present study found that RRM1-negative was significantly associated with prolonged OS.…”
Section: Discussioncontrasting
confidence: 64%
“…For example, several retrospective studies have evaluated the association between RRM1 expression and survival outcomes in patients with BTC. Although two studies found that low RRM1 expression was significantly associated with prolonged OS [23,24], two other studies found no significant differences between patients with high and low RRM1 expression [15,25]. The present study found that RRM1-negative was significantly associated with prolonged OS.…”
Section: Discussioncontrasting
confidence: 64%